The Effectiveness of Using Canva as a Learning Medium in Improving High School Students' Learning Outcomes - Putri Nuraini; Agung Setiawan; Fauzi Erwis (EDUJAVARE: International Journal of Educational Research, 2026)
Digital transformation in education requires innovative instructional media that can improve student learning outcomes, including Canva as an interactive visual platform. This study examined the effectiveness of Canva in improving the learning outcomes of Grade XI students in Information and Communication Technology (ICT) at SMA Negeri 1 Hutaraja Tinggi. A quantitative approach with a pretest-posttest control group design was employed. The sample comprised 40 students, with 20 students in the experimental class and 20 in the control class. Data were analyzed using normalized gain (N-Gain). The findings revealed a clear difference between the two groups. The experimental class achieved a mean N-Gain of 85.38%, categorized as high, whereas the control class achieved 69.81%, categorized as moderate. These findings indicate that Canva is effective in improving students' learning outcomes. The study provides practical implications for teachers seeking to develop more interactive and engaging digital instructional media, particularly for ICT instruction at the senior high school level.